Analisis Jaringan Komputer Local Area Network (LAN) di SMKN 1 Negeri Agung Menggunakan Metode PPDIOO - Sandi, Boy; Sriyanto, Sriyanto; Novita, Rini (Universitas Labuhanbatu, 2024)
This research aims to analyze the performance of the Local Area Network (LAN) computer network at SMKN 1 Negeri Agung using the PPDIOO Method. The PPDIOO method is an approach used in network management and development. This research was conducted to ensure that computer networks in schools can support learning and administrative activities efficiently. The PPDIOO method aims to analyze the performance of the Local Area Network (LAN) computer network at the SMKN 1 Negeri Agung Vocational School. This analysis was carried out by applying the PPDIOO Method (Prepare, Plan, Design, Implement, Operate, Optimize) as a guide for the network management life cycle. The aim of conducting computer network analysis is to find out the process of the working system on a computer network and to find out the advantages and disadvantages of a computer network system. Apart from that, you can find out the topology of the computer network at SMKN 1 Negeri Agung. The network is expected to provide insight for schools to improve network efficiency to support a more effective and quality learning process. Computer Network Analysis was carried out by direct observation and simulation using Cisco Pracket Tracer at the Computer Laboratories at SMKN 1 Negeri Agung. The results can measure and analyze network performance, including data transmission speed, latency, and reliability.